Physical, chemical, and microbiological characteristics of groundwater in Los Chiles, Costa Rica, and its association with land use (UNED Research Journal, 2023)
“Physical, chemical, and microbiological characteristics of groundwater in Los Chiles, Costa Rica, and its association with land use”. Introduction: Los Chiles has one of the lowest Social Progress Indexes in Costa Rica. The inhabitants drink untreated groundwater from an aquifer across the Nicaragua-Costa Rica border. Objective: To characterize water quality and possible associations with land use. Methods: We collected six water samples from wells during the dry and rainy seasons in 2019 and applied standard tests. Results: Grasslands and bare ground cover larger areas than other land uses. The water is calcic-bicarbonate type, and its physical-chemical values are acceptable, we did not detect Escherichia coli in any sample, while we only detected fecal coliforms in La Trocha. Conclusion: If treated to eliminate coliforms and protected from other effects of human activity, this water will be optimal for human consumption.
Keywords: groundwater; environmental health; waterborne diseases; hydric resource